MON-494 Quality of Life in Patients with Papillary Thyroid Microcarcinoma According to the Treatment: Total Thyroidectomy Versus Total Thyroidectomy with Radioactive Iodine Remnant Ablation - Ahn, Jonghwa (J Endocr Soc, 2020)
Background: Recently, the role of radioactive iodine (RAI) ablation in the treatment of low risk differentiated thyroid carcinoma (DTC), especially for papillary thyroid microcarcinoma (PTMC), is controversial. This study aims to compare quality of life (QoL) parameters in patients with PTMC underwent total thyroidectomy (TT) versus TT with RAI ablation. Methods: In this cross-sectional study, patients with PTMC who underwent TT with/without RAI remnant ablation were prospectively enrolled between June 2016 and October 2017. All patients completed three questionnaires: 12-item short-form health survey (SF-12), thyroid cancer specific quality of life (THYCA-QOL), and fear of progression (FoP). Results: The TT and TT with RAI groups comprised 107 and 183 patients, respectively. The TT with RAI group had significantly lower serum TSH level than TT group. However, after matching of TSH level between the groups (TT with RAI = 100, TT = 100), there was no significant difference in baseline characteristics. According to the SF-12, the score for general health showed significantly lower in TT with RAI group than TT group (p = 0.047). The THYCA-QOL also showed statistically significant difference in felt chilly score between the groups (p = 0.023). No significant differences in FoP scores were seen between the groups. Conclusion: Patients with PTMC underwent TT with RAI ablation experienced more health-related problems than those managed by TT alone. These findings support RAI ablation should be carefully determined in patients with low-risk DTCs.